The environmental dependence of the structure of outer galactic discs in STAGES spiral galaxies - Maltby, D; Gray, M; Aragón-Salamanca, A; Wolf, C; Bell, E; Jogee, S; Haeussler, B; Barazza, F; Boehm, A; Jahnke, K (2011)
We present an analysis of V-band radial surface brightness profiles for spiral galaxies from the field and cluster environments using Hubble Space Telescope/Advanced Camera for Surveys imaging and data from the Space Telescope A901/2 Galaxy Evolution Survey (STAGES). We use a large sample of ~330 face-on to intermediately inclined spiral galaxies and assess the effect of the galaxy environment on the azimuthally averaged radial surface brightness mu profiles for each galaxy in the outer stellar disc (24 < mu < 26.5 mag per sq arcsec). For galaxies with a purely exponential outer disc (~50 per cent), we determine the significance of an environmental dependence on the outer disc scalelength h_out. For galaxies with a broken exponential in their outer disc, either down-bending (truncation, ~10 per cent) or up-bending (anti-truncation, ~40 per cent), we measure the strength T (outer-to-inner scalelength ratio, log_10(h_out/h_in) of the mu breaks and determine the significance of an environmental dependence on break strength T. Surprisingly, we find no evidence to suggest any such environmental dependence on either outer disc scalelength h_out or break strength T, implying that the galaxy environment is not affecting the stellar distribution in the outer stellar disc. We also find that for galaxies with small effective radii (r_e < 3 kpc) there is a lack of outer disc truncations in both the field and cluster environments. Our results suggest that the stellar distribution in the outer disc of spiral galaxies is not significantly affected by the galaxy environment.